Hyperbilirubinemia in atazanavir treated HIV-infected patients: the impact of the UGT1A1*28 allele - Panagopoulos P; Maltezos E; Hatzakis A; Paraskevis D (Dove Medical Press, 2017)
Periklis Panagopoulos,1 Efstathios Maltezos,1 Angelos Hatzakis,2 Dimitrios Paraskevis2 12nd Department of Internal Medicine, Democritus University of Thrace, Alexandroupoli, Greece; 2Department of Hygiene, Epidemiology and Medical Statistics, Medical School, National and Kapodistrian University of Athens, Athens, Greece Abstract: Combination antiretroviral treatment (cART) has significantly improved the life expectancy of people living with HIV. The life-long nature of cART increases the risk of side effects, which in some cases may have been caused by specific genetic characteristics. Patients treated with atazanavir (ATV) boosted with ritonavir (rit), which is a protease inhibitor used for the treatment of HIV, present with elevated bilirubin levels, at high proportions. ATV/rit-related hyperbilirubinemia has been previously associated with genetic characteristics in uridine diphosphate glucuronosyltransferase (UGT) enzyme. The prevalence of the UGT1A1*28 variant, which is the most frequent polymorphism in the UGT1A1 superfamily, has been found to range between 9% and ~60% with the highest frequency in Africa. Pharmacokinetics for additional HIV drugs, such as the integrase inhibitors Raltegravir and Elvitegravir, has been also shown to be influenced by UGT1A1 polymorphisms. Pharmacogenetics/pharmacogenomics testing can be useful to identify a patient’s susceptibility to drug toxicity and therefore to facilitate selection of the optimal long-term suppressive regimen. Keywords: atazanavir, hyperbilirubinemia, pharmacogenomics